2015
DOI: 10.1002/cne.23874
|View full text |Cite|
|
Sign up to set email alerts
|

Cryptic laminar and columnar organization in the dorsolateral pallium of a weakly electric fish

Abstract: In the weakly electric gymnotiform fish, Apteronotus leptorhynchus, the dorsolateral pallium (DL) receives diencephalic inputs representing electrosensory input utilized for communication and navigation. Cell counts reveal that, similar to thalamocortical projections, many more cells are present in DL than in the diencephalic nucleus that provides it with sensory input. DL is implicated in learning and memory and considered homologous to medial and/or dorsal pallium. The gymnotiform DL has an apparently simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 79 publications
2
74
0
Order By: Relevance
“…Because fish lack an isocortex, the ability of cross-modal object recognition cannot depend on the existence of these mammalian brain structures per se. However, a recent study has shown a cryptic laminar and columnar organization of the dorsolateral pallium (DL) of a gymnotiform weakly electric fish which, together with other organizational structures, supports the hypothesis that there is a homology between the teleost DL and the mammalian cortex (34). Furthermore the pallium of G. petersii is known to receive inputs from the auditory, the visual, the electrosensory, and the lateral line systems (35), and lesion experiments in goldfish have shown that the teleost telencephalon is involved in spatial learning tasks (36)(37)(38), making it a prime candidate for the location of cross-modal object recognition in G. petersii.…”
Section: Discussionmentioning
confidence: 87%
“…Because fish lack an isocortex, the ability of cross-modal object recognition cannot depend on the existence of these mammalian brain structures per se. However, a recent study has shown a cryptic laminar and columnar organization of the dorsolateral pallium (DL) of a gymnotiform weakly electric fish which, together with other organizational structures, supports the hypothesis that there is a homology between the teleost DL and the mammalian cortex (34). Furthermore the pallium of G. petersii is known to receive inputs from the auditory, the visual, the electrosensory, and the lateral line systems (35), and lesion experiments in goldfish have shown that the teleost telencephalon is involved in spatial learning tasks (36)(37)(38), making it a prime candidate for the location of cross-modal object recognition in G. petersii.…”
Section: Discussionmentioning
confidence: 87%
“…The similarities to the findings of Wang et al [20] are quite remarkable and further support the hypothesis of the antiquity of radial microcircuitry and the shared cell and circuit properties of avian and mammalian brains. Recent studies by Maler and co-workers [22] have revealed the presence of similar radially organized microcircuits, mediating electroreception, in the telencephalon of teleost fish. Further studies of the DVR telencephalic circuitry of non-avian reptiles as well as amphibia are clearly needed.…”
Section: Microcircuitry Of the Avian Telencephalon Revealed Radial/comentioning
confidence: 98%
“…In mammals, the primary sensory areas of the neocortex present the highest basal CO activity, whereas the limbic and association areas present only low to moderate basal CO levels [Wallace, 1987;Hevner et al, 1995]. Interestingly, it has recently been reported that the teleost Dld is organized in cryptic layers and columns with highly localized intrinsic connectivity, resembling more the mammalian sensory cortex than the hippocampus [Trinh et al, 2016].…”
Section: The DLV But Not the Dld Is Activated With Spatial Trainingmentioning
confidence: 99%
“…However, Elliott et al [2017] [Rodríguez et al, 2002;Broglio et al, 2010], do not support this proposal. In fact, the highly localized intrinsic connectivity and the expansive input representation in the Dld described in the studies of Elliott et al [2017] and Trinh et al [2016] are more compatible with a multistage heteroassociative network structure that performs competitive learning and pattern association, as in the sensory neocortex, than with the spatially extensive autoassociative architecture of the hippocampus that enables the formation of relational and episodic memories [Amaral and Lavenex, 2007;Rolls and Treves, 1998;Rolls, 2013].…”
Section: The DLV But Not the Dld Is Activated With Spatial Trainingmentioning
confidence: 99%